Understanding Emotion Inflexibility in Risk for Affective Disease: Integrating Current Research and Finding a Path Forward - Coifman, Karin G.; Summers, Christopher B. (Frontiers in Psychology, 2019)
Emotion-related disorders (e.g., depression, anxiety, stress, eating, substance and some personality disorders) include some of the most common, burdensome, and costly diseases worldwide. Central to many, if not all of these disorders may be patterns of rigid or inflexible emotion responses. Indeed, theorists point to emotion inflexibility as a potential cause or maintaining factor in emotion-related diseases. Despite the increasing prominence of emotion inflexibility in theories of affective disease, a comprehensive review of the developing empirical literature has not yet been conducted. Accordingly, this review will examine the three dominant lines of inquiry assessing emotion flexibility. These include: 1) the capacity to use and vary deliberate emotion regulation strategies, 2) the context-sensitivity of spontaneous emotional responses, and 3) flexibility in the appraisal of emotional events and experiences. Moreover, current evidence suggests that each of these three lines of research may converge to suggest the interplay of two key biological dimensions in emotion inflexibility, threat sensitivity and cognitive control, known to be impaired in patients with affective disorders. In short, this developing body of work suggests a path by which future research could explicate and even exploit the ties between emotion inflexibility and affective disease, contributing to the development of improved models of risk, assessment, and intervention, with broad implications for psychological health.